CLINICAL EXPERIENCE WITH DLBS3233, A COMBINATION OF CINNAMOMMUM BURMANNII AND LAGERSTROEMIA SPECIOSA, FOR POLYCYSTIC OVARY SYNDROME TREATMENT - Kartolo, Darsono; Tjandrawinata, Raymond R.; Suparman, Eddy; Susanto, Liana W.; Suparman, Erna (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: DLBS3233, a new insulin sensitizing agent for Type 2 diabetes, is a combination-bioactive-fraction derived from two herbs, i.e., Lagerstroemia speciosa and Cinnamomum burmannii. Since insulin resistance plays a central pathogenic role in polycystic ovary syndrome (PCOS), DLBS3233 has the potential to benefit women with such a condition, in whom menstrual irregularity, chronic anovulation or infertility are manifested. This clinical study was performed to evaluate the clinical efficacy of DLBS3233 as a single pharmacological therapy in improving follicle maturity in women with PCOS measured by a transvaginal ultrasonography (USG). Methods: The open study enrolled 14 PCOS subjects from the Obstetrics and Gynecology Department of Sam Ratulangi University/Prof. Dr. Kandou Hospital, satellite hospitals, and private practices. Patients were measured for the dominant follicle diameter using transvaginal USG. Subjects were given DLBSS3233 capsule at a dose of 1 capsule at 100 mg once daily for 30 days of the treatment. At the end of the study, patients' follicle diameters were re-assessed. The difference in follicle diameters was compared within the group (within-subject) by paired t-test, with a significance level (Î±) of 0.05. Results: Among 14 PCOS enrolled subjects, 57.2% aged between 26 and 30 years old. There were similar proportions of subjects with normal body mass index (42.8%) and overweight(42.8%). Before treatment (at baseline), the mean follicle diameter was 4.094Â±1.016 mm. After 30 days of treatment, it increased significantly to 8.594Â±1.647 mm (p<0.001 versus baseline). There were 10 subjects (71.4%) showed follicles with size ranging between 5 and 10 mm, while the remaining 4 subjects (28.6%) had them bigger than 10 mm. Conclusion: Through this study, DLBS3233 at the dose of 100 mg once daily for 30 days showed a potential benefit for PCOS patients, particularly in improving follicle maturity expressed as an increased follicular diameter. Keywords: DLBS3233, Cinnamomum burmannii, Follicle diameter, Lagerstroemia speciosa, Polycystic ovary syndrome.